An Empirical Investigation of IPO Underpricing in Japanese Stock Market - HUANG, SHAOJIE (2014)
In general, IPO underpricing is much lower in developed countries than developing countries. However, Japan is developed country with mature stock market, which has a high level of IPO underpricing. This is abnormal. Hence, this dissertation tries to investigate the driving factors in Japanese IPO underpricing by using a data sample of all 1561 IPOs issued in Japanese IPO market from 1997 to 2009. The initial return of new issues is used to measure the level of underpricing. Based on previous literatures and characteristics of Japanese IPO market, a multiple linear regression model is created with ten independent variables, consisting of offer size, offer price, frim age, underwriters’ reputation, offer price position, percent width of offer price range, high-tech industry, bull market, bear market and secondary offering percentage.